2*x+69*2=69*4
47*(27-x)47
Bài 2 : Tìm x, biết :
a, ( x - 12 ) x 105 = 0
b, 2 x x - 69 x 2 = 69 x 4
c, 47 x ( 27 - x) = 47
d, 2 x x - 12 + x = 0
Ai nhanh nhất tick 3 tick
P/s : làm từng phần sợ bn ko đợi đc :D
a) ( x - 12 ) x 105 = 0
mà 105 khác 0
=> x - 12 = 0
=> x = 12
b)
2 x x - 69 x 2 = 69 x 4
2 x ( x - 69 ) = 276
x - 69 = 138
x = 207
a) x - 12 = 0 => x = 12
b) 2x = 69. (4+2)
=> 2x = 69. 6
=> x = 69.3 = ...
c) 27 - x = 47 : 47 = 1
=> x = 27 - 1 = 26
d) 3.x - 12 = 0
=> x = 12 : 3 = 4
Tìm x :
a, (x - 12).105 = 0
b, 47.(27-x) = 47
c, 2x + 69.2 = 69 .4
d, 2x - 12 -x =0
a, => x-12 = 0
=> x=12
b, => 27-x =1
=> x= 27-1 -26
c, => 2x = 69(4-2) =69.2
=> x=69
d, => x-12=0
=> x=12
a) (x - 12) . 105 = 0
=> x - 12 = 0
=> x = 12
b) 47 . (27 - x) = 47
=> 27 - x = 1
=> x = 27 - 1 = 26
c) 2x + 69 . 2 = 69 . 4
=> 2x = 69 . 4 - 69 . 2
=> 2x = 69 . (4 - 2) = 69 . 2
=> x = 69 . 2 : 2
=> x = 69
d) 2x - 12 - x = 0
=> x - 12 = 0
=> x = 12
a ) ( x - 12 ) x 105 = 0
x - 12 = 0 : 105
x - 12 = 0
x = 0 + 12
x = 12
b ) 47 x ( 27 - x ) = 47
27 - x = 47 : 47
27 - x = 1
x = 27 - 1
x = 26
c ) 2x + 69 x 2 = 69 x 4
2x + 138 = 276
2x = 276 - 138
2x = 138
x = 138 : 2
x = 69
d ) 2x - 12 - x = 0
2x - x = 0 + 12
x = 12
69 x 113 - 27 x 69 + 69 x 14 + 31
= 69 x ( 113 - 27 + 14 ) + 31
= 69 x 100 +31
= 6900 + 31
=6931
=69x(113-27+14)+31
=69x100+31
=6900+31
=6931
69 x 113 - 27 x 69 + 69 x 14 + 31
= 69 x ( 113 - 27 + 14 ) + 31
= 69 x 100 + 31
= 6900 + 31
= 6931
g) (15 + 37) + (52 – 37 – 17) h) (38 – 42 +14) - (38 – 42 - 15) i) (27 + 65 ) + (346 - 27- 65) k) - (27 + 65) - (346 – 27 - 65) l) (42 – 69 + 17) - (42 + 17) m) 24. (16 - 5) – 16. (24 – 5 ) n) (-12). 47 – 12 . 52 + (-12) p) 51 . (69 - 25) – 69. (51 - 25) |
g) (15 + 37) + (52 – 37 – 17) = 15 + 37 + 52 – 37 – 17 = 15 + 52 – 17 = 50 h) (38 – 42 +14) - (38 – 42 - 15) = 38 – 42 +14 - 38 + 42 + 15 = 14 + 15 = 29 i) (27 + 65 ) + (346 - 27- 65) = 27 + 65 + 346 - 27- 65 = 346 k) - (27 + 65) - (346 – 27 - 65) = -27 - 65 - 346 + 27 + 65 = -346 l) (42 – 69 + 17) - (42 + 17) = 42 – 69 + 17 - 42 - 17 = – 69 m) 24. (16 - 5) – 16. (24 – 5 ) = 24. 16 - 24 . 5 - 16 . 24 + 16. 5 = - 24 . 5 + 16. 5 = -8 . 5 = -40 n) (-12). 47 – 12 . 52 + (-12) = -12 (47 - 52 + 1) = -12 . (-4) = 48 p) 51 . (69 - 25) – 69. (51 - 25) = 51 . 69 - 51 . 25 – 69. 51 + 69. 25 = - 51 . 25 + 69. 25 = (- 51+ 69).25 = 450 |
Bài 1:
a) -|-8|+(-7)-(19)
b) (38-22+15)-(-22+38)
c) -15.63-(-63).115
d) -13-(-7)+|-8|
e) -(-116+27-87)+(-116+27)
f)47.(-69)+31.(-47)
Bài 2:
a) -(+72)+x=-(-27)
b) |15-x|=-(-37)
c) -15-x=-(+8)
d) |x-11|=-15+27
(Mọi người giúp mình hai bài này nha,năn nỉ luôn đó)
a) 25. 69 + 31. 25 – 150;
b) 198 : [130 – (27 – 19 )2] + 20210 ;
c) 520 : (515.15 + 515.10).
d) 27– (15 – 31) – (– 2 + 21+ 5)
e) 47 – (23 + 17) – (– 17 + 47)
f) 34 – [(–12) + 34] – (49 + 12) g) 72 – (15 – 14 + 72) + 52
a: =25x100-150=2500-150=2350
c: \(=520:\left\{515\cdot25\right\}\)
=104/2575
so sanh 27 mũ 47 và 8 mũ 69
27^47= (3^3)^47 (1)
8^69= (2^3)^69 (2)
Từ (1) và (2)=> 27^47>8^69
a=71/69+60/47+67/69+34/47
a=71/69+60/47+67/69+34/47
=71/69+67/69+60/47+34/47
=138/69+94/47
=2+2
=4